Setting and Adversary: The Role of Nature in Horacio Quiroga’s Jungle Tales - Chen, Yiru (Journal of Social Science and Humanities, 2025)
Renowned as the founder of Latin American short stories, Horacio Quiroga is celebrated for his literary exploration of the relationship between man and nature. In his jungle tales, his meticulously precise descriptions depict a jungle world tainted by horror, illness, and suffering in which humanity is deeply immersed. In this context, nature serves both as the setting where characters interact and as the adversary with whom they struggle for survival. This paper seeks to examine the dual role of nature in these tales by analyzing the two functions it performs.